The effects of ventilation pattern on carbon dioxide transfer in three computer models of the airways. - Whiteley, J; Turner, M; Baker, AB; Gavaghan, D; Hahn, C (2002)
We investigate the effects on arterial P(CO(2)) and on arterial-end tidal P(CO(2)) difference of six different ventilation patterns of equal tidal volume, and also of various combinations of tidal volume and respiratory rate that maintain a constant alveolar ventilation. We use predictions from three different mathematical models. Models 1 (distributed) and 2 (compartmental) include combined convection and diffusion effects. Model 3 incorporates a single well-mixed alveolar compartment and an anatomical dead-space in which plug flow occurs. We found that: (i) breathing patterns with longer inspiratory times yield lower arterial P(CO(2)); (ii) varying tidal volume and respiratory rate so that alveolar ventilation is kept constant may change both PA(CO(2)) and the PA(CO(2))-PET(CO(2)) difference; (iii) the distributed model predicts higher end-tidal and arterial P(CO(2)) than the compartmental models under similar conditions; and (iv) P(CO(2)) capnograms predicted by the distributed model exhibit longer phase I and steeper phase II than other models.